Professional Decline and Resistance: The Case of Library and Archives Canada - Oliphant, Tami; McNally, Michael B. (Radical Teacher, 2014)
In 2004, Canada was the first country in the world to amalgamate its two main documentary heritage institutions, the National Archives of Canada (established in 1872) and the National Library of Canada (established in 1953) into one "modernized" institution: Library and Archives Canada (LAC). The "modernization" policy has commercialized and reduced services, collections, and collaboration while simultaneously deprofessionalizing and casualizing the work of professionals. Resistance to modernization has come from many stakeholders across Canada but the responses by the Canadian Association of University Teachers (CAUT) and the Canadian Library Association (CLA) are particularly salient. Both are national organizations concerned with access to information and Canada’s documentary heritage. The case of LAC demonstrates how a neoliberal remaking of one prominent, national institution can weaken entire professions.